Heterogeneous polydentate mobile chelating node to detect breach in surveillance sensor network. Issue 6 (9th June 2021) - Misra, Sudip; Goswami, Sumit; Taneja, Chaynika; Kar, Pushpendu
Abstract: Nature inspired algorithms are common in routing and security in mobile wireless sensor networks (WSN). While most of the existing algorithms are bio‐inspired, chemistry inspired security algorithms are rare. Chelation is a chemical process where a molecule forms two or more bonds with an atom or a molecule to hold it strongly. Analogous to this chemical process, a chelating node in a mobile WSN is defined as a mobile node that forms more than one logical association with another node. The paper uses mobile polydentate chelating node, which uses multiple heterogeneous logical linkages with a rogue node, to ascertain non‐friendly behavior of a node to ensure detection and removal. The multiple linkage processes are based on challenge‐response using public key infrastructure, integrity of routing algorithm, routing table fidelity and data path tracking. This n‐dentation ensures detection of captured nodes as well as nodes planted by adversaries. The paper demonstrates the applicability of this process for a mobile WSN‐based border surveillance where the number of attacks is high and varied in its pattern. The proposed approach reduces false negative as well as false positive detection by its n‐modular redundancy. Simulation results are presented to illustrate the effectiveness of this scheme.